The Influence Of Work Life Balance On Job Satisfaction Of Housekeeping Employee At Renaissance Bali Uluwatu Resort & Spa - Ni Putu Anggy Kecana Dewi; Irene Hanna H. Sihombing; I Dewa Putu Hendri Pramana (International Journal of Applied Sciences in Tourism and Events, 2021)
Human resources are the main capital to achieve company’s goals in hospitality industry. One important thing that company should consider in maintaining employee performance is a job satisfaction. Employee that does not have a job satisfaction while working will gradually decrease the employee performance. Many factors influence job satisfaction one of them is work life balance. The low work life balance resulted a low job satisfaction. This research aims at investigating the influence of work life balance  on employee job satisfaction to housekeeping employee at Renaissance Bali Uluwatu Resort & Spa. Respondents in this research were 35 housekeeping employees with saturated sampling. The data collection was done by distributing the questionnaire using a Likert scale that use 5 points to measure 30 item statements. The data analysis techniques used was simple linear regression, t-test, and determination coefficient test which was assisted by SPSS version 23 for Windows.  The results of this research indicated that work life balance (X)  partially has a positive and significant effect on housekeeping employee job satisfaction (Y) at Renaissance Bali Uluwatu Resort & Spa with a value of tcount > ttable = 9,840 > 2,032. Work life balance contributes to influence Employee job satisfaction of  74,6% in strong catagories, while the remaining 25,4% is influenced by other factors outside of this research. This research is expected to be used as a consideration to pay more attention of employee work life balance to increase employee job satisfaction.